9x+6(3x-4)=12-9x

Simple and best practice solution for 9x+6(3x-4)=12-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+6(3x-4)=12-9x equation:


Simplifying
9x + 6(3x + -4) = 12 + -9x

Reorder the terms:
9x + 6(-4 + 3x) = 12 + -9x
9x + (-4 * 6 + 3x * 6) = 12 + -9x
9x + (-24 + 18x) = 12 + -9x

Reorder the terms:
-24 + 9x + 18x = 12 + -9x

Combine like terms: 9x + 18x = 27x
-24 + 27x = 12 + -9x

Solving
-24 + 27x = 12 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-24 + 27x + 9x = 12 + -9x + 9x

Combine like terms: 27x + 9x = 36x
-24 + 36x = 12 + -9x + 9x

Combine like terms: -9x + 9x = 0
-24 + 36x = 12 + 0
-24 + 36x = 12

Add '24' to each side of the equation.
-24 + 24 + 36x = 12 + 24

Combine like terms: -24 + 24 = 0
0 + 36x = 12 + 24
36x = 12 + 24

Combine like terms: 12 + 24 = 36
36x = 36

Divide each side by '36'.
x = 1

Simplifying
x = 1

See similar equations:

| 3a-11=4(a+1)+13a+3 | | 2g-8+3g=7 | | .17(x+29)=86 | | 2x-6=5x+27 | | 2y^2-7y-10=0 | | 4x-2(.50-1)=14 | | 101(87+13)= | | y^3+729= | | 4x-2(x-2)=-7+4x+5 | | 9x-12=84 | | 4(2x-3)=30 | | 15-12z=21 | | .17(x-29)=86 | | 2x=1-5 | | 7(x+2)=5(x+14) | | p-4=-1+2P | | 4m+8m=84 | | 2(m-8)=12 | | 9k(8k+7)= | | 10x+44=2(8x-23) | | T+4=120 | | 10-2x=-2y | | 77x^2-145+50= | | 9(x-7)+54=9x-8 | | 2(m-8)=54 | | 16-n=2n+8+5n | | 48+3x=246-15x | | 6x+4=1x-11 | | 7x-20=4x+30 | | 3(x+9)=60 | | 7+2x-10=x+2 | | 105+9.50r=14.75r |

Equations solver categories